2021
DOI: 10.3390/ph15010021
|View full text |Cite
|
Sign up to set email alerts
|

Atazanavir Is a Competitive Inhibitor of SARS-CoV-2 Mpro, Impairing Variants Replication In Vitro and In Vivo

Abstract: Atazanavir (ATV) has already been considered as a potential repurposing drug to 2019 coronavirus disease (COVID-19); however, there are controversial reports on its mechanism of action and effectiveness as anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Through the pre-clinical chain of experiments: enzymatic, molecular docking, cell-based and in vivo assays, it is demonstrated here that both SARS-CoV-2 B.1 lineage and variant of concern gamma are susceptible to this antiretroviral. Enzymati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 33 publications
1
29
0
1
Order By: Relevance
“…This is probably due to their impact on the orientation of the compounds inside the enzyme target, which was supported by the experimental evidence in the inhibitory percentage of kaempferol, quercetin, and myricetin (10 μM) to SARS-CoV-2 M pro . The EC 50 value for myricetin was comparable to that of atazanavir (ATV), a repurposed SARS-CoV-2 inhibitor that targets M pro [ 27 ], reinforcing the good prospects of flavonols as SARS-CoV-2 antivirals. The CC 50 value in most cases is about 60 times higher than the EC 50 value, which provided a selective index (SI) consistent with an adequate safety profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is probably due to their impact on the orientation of the compounds inside the enzyme target, which was supported by the experimental evidence in the inhibitory percentage of kaempferol, quercetin, and myricetin (10 μM) to SARS-CoV-2 M pro . The EC 50 value for myricetin was comparable to that of atazanavir (ATV), a repurposed SARS-CoV-2 inhibitor that targets M pro [ 27 ], reinforcing the good prospects of flavonols as SARS-CoV-2 antivirals. The CC 50 value in most cases is about 60 times higher than the EC 50 value, which provided a selective index (SI) consistent with an adequate safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…The inoculum was removed, and cells were incubated with different concentrations of genistein, apigenin, luteolin or fisetin (0.00, 0.63, 1.25, 2.50, 5.00, and 10.0 μM), kaempferol, myricetin, or quercetin (0.00, 0.10, 0.30, 1.00, 3.16, and 10.0 μM), and RDV (0.00, 0.0001, 0.001, 0.01, 0.10, 0.50, 1.0, 5.0, and 10.0 μM) in DMEM with 10% FBS. After 48 h, the virus content in the supernatant was quantified by plaque forming assays in Vero cells (2.0 × 10 4 cells/well) according to our previous publications [ 10 , 27 , 28 ]. The virus titers were calculated by scoring for plaque-forming units (PFU/mL); and non-linear regression analysis of the dose–response curves were also performed to calculate the 50% effective concentration (EC 50 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following molecular docking studies, which showed that atazanavir has a strong binding affinity to the main protease of SARS-CoV-2 [ 50 ] and further demonstrating high bioavailability within the respiratory tract [ 51 ], atazanavir was deemed an interesting candidate for anti-SARS-CoV-2 activity, and was used in in vivo studies of humanized murine models of SARS-CoV-2 infection [ 50 ]. In these studies, it improved survival in atazanavir-treated groups, compared with non-treated controls.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it showed sufficient anti-inflammatory activity, significantly reducing the levels of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and keratinocyte-derived chemokines (KCs) in the lungs of treated mice. Atazanavir further protected animals from severe lung injury, which could lead to hemorrhage and shrinking of the lobe, bronchiole, and alveoli, which was prominent in untreated groups [ 50 ].…”
Section: Introductionmentioning
confidence: 99%